Spatial Imaginaries and Tech Cities: Place-branding East London's digital economy. (8th May 2018) - Nathan, Max; Vandore, Emma; Voss, Georgina
Abstract: We explore place branding as an economic development strategy for technology clusters, using London's 'Tech City' initiative as a case study. We site place branding in a larger family of policies that develop spatial imaginaries and specify affordances and constraints on place brands and brand-led strategies. Using mixed methods over a long timeframe, we analyse Tech City's emergence and the overlapping, competing narratives that preceded and succeeded it, highlighting day-to-day challenges and more basic tensions. While a strong brand has developed, we cast doubt on claims that policy has had a catalytic effect, at least in the ways originally intended.